2021
DOI: 10.1038/s41598-021-98548-x
|View full text |Cite
|
Sign up to set email alerts
|

Broad scale proteomic analysis of heat-destabilised symbiosis in the hard coral Acropora millepora

Abstract: Coral reefs across the globe are threatened by warming oceans. The last few years have seen the worst mass coral bleaching events recorded, with more than one quarter of all reefs irreversibly impacted. Considering the widespread devastation, we need to increase our efforts to understanding the physiological and metabolic shifts underlying the breakdown of this important symbiotic ecosystem. Here, we investigated the proteome (PRIDE accession # PXD011668) of both host and symbionts of the reef-building coral A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 98 publications
(138 reference statements)
7
28
1
Order By: Relevance
“…Several enzymes involved in oxidative stress response were at higher abundance in both the OL and IC of bleached M. capitata compared to samples from non-bleached corals. This observation is consistent with proteomics (e.g., Weston et al, 2015;Cziesielski et al, 2018;Petrou et al, 2021) and transcriptomics (e.g., DeSalvo et al, 2008DeSalvo et al, , 2010Voolstra et al, 2009) studies that have demonstrated increased antioxidant activity in response to thermal stress in cnidarians. Multiple catalases (CAT) were elevated in the OL and IC of bleached corals.…”
Section: Response To Oxidative Stresssupporting
confidence: 89%
See 3 more Smart Citations
“…Several enzymes involved in oxidative stress response were at higher abundance in both the OL and IC of bleached M. capitata compared to samples from non-bleached corals. This observation is consistent with proteomics (e.g., Weston et al, 2015;Cziesielski et al, 2018;Petrou et al, 2021) and transcriptomics (e.g., DeSalvo et al, 2008DeSalvo et al, , 2010Voolstra et al, 2009) studies that have demonstrated increased antioxidant activity in response to thermal stress in cnidarians. Multiple catalases (CAT) were elevated in the OL and IC of bleached corals.…”
Section: Response To Oxidative Stresssupporting
confidence: 89%
“…Proteomics has proven to be a valuable tool for uncovering active cellular processes and elucidating the response of different biological compartments of symbiotic cnidarians in response to stress (Weston et al, 2015;Ricaurte et al, 2016;Cziesielski et al, 2018;Hernández-Elizárraga et al, 2019;Mayfield, 2020;Mayfield et al, 2021;Petrou et al, 2021). Our high-throughput discovery-based proteomic analyses of the OL and IC of bleached and non-bleached corals support our hypothesis that proteomic signatures differ between M. capitata OL and IC, reflecting different biological functions associated with these two compartments.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As the main consequence of climate change, ocean warming is seriously threatening the survival of coral reefs [3]. Many studies have been conducted to explore the response patterns of corals to the elevated temperature by diverse methods [4][5][6]. For example, divergent responses to heat stress by different coral taxa has been found in the Great Barrier Reef, resulting in the regional-scale shift in the composition of coral assemblages [7].…”
Section: Introductionmentioning
confidence: 99%